Faktor yang Mempengaruhi Regulasi Emosi Siswa SD dalam Menghadapi Perundungan: Kajian Literatur Sistematis - Annisa Rizekiati; Nida Hasanati (JURNAL BIMBINGAN DAN KONSELING AR-RAHMAN, 2026)
Bullying in elementary schools is a serious problem that has a negative impact on students’ mental health and academic performance. Emotional regulation skills are key for children in monitoring, evaluating, and modifying their emotional reactions when facing these psychosocial impacts. This study aims to investigate the dominant internal and external factors influencing emotional regulation in elementary school students, as well as to map the role of the school environment. The method used was a Systematic Literature Review (SLR) based on the Rayyan instrument, analyzing 27 relevant research journals from 2013 to 2026. The review results indicate that internally, this ability is influenced by students’ cognitive maturity, emotional awareness, and temperament. Externally, the family environment plays the most dominant role, where parental emotional warmth, parenting skills, and secure attachment significantly enhance children’s emotional regulation capacity. At school, the principal’s anti-bullying policies, along with teachers’ moral support and emotional literacy, contribute positively as protective factors. Various interventions such as psychoeducation, role-playing, and music therapy have also been proven effective in improving students’ emotional stability. This study concludes the importance of strong synergy between parents and educators to build a resilient emotional foundation for children. ____________________________________________________________________Perundungan di sekolah dasar merupakan masalah serius yang berdampak buruk terhadap kesehatan mental dan prestasi akademik siswa. Kemampuan regulasi emosi menjadi kunci utama bagi anak dalam memonitor, mengevaluasi, dan memodifikasi reaksi emosional saat menghadapi dampak psikososial tersebut. Penelitian ini bertujuan menginvestigasi faktor internal dan eksternal dominan yang mempengaruhi regulasi emosi siswa sekolah dasar, serta memetakan peran lingkungan sekolah. Metode yang digunakan adalah Systematic Literature Review (SLR) berbasis instrumen Rayyan terhadap 27 jurnal penelitian relevan dari rentang tahun 2013 hingga 2026. Hasil tinjauan menunjukkan bahwa secara internal, kemampuan ini dipengaruhi oleh kematangan kognitif, kesadaran emosional, dan temperamen siswa. Secara eksternal, lingkungan keluarga memegang peranan paling dominan di mana kehangatan emosional orang tua, keterampilan pengasuhan, dan keterikatan aman secara signifikan meningkatkan kapasitas regulasi emosi anak. Di sekolah, kebijakan anti-perundungan kepala sekolah serta dukungan moral dan literasi emosi guru berkontribusi positif sebagai faktor pelindung. Berbagai intervensi seperti psikoedukasi, bermain peran, dan terapi musik juga terbukti efektif meningkatkan stabilitas emosi siswa. Penelitian ini menyimpulkan pentingnya sinergi kokoh antara orang tua dan pendidik untuk membangun fondasi emosional anak yang tangguh.